Elements of Metamorphic Rocks (Marble and Quartzite) of Bukit Cinta Gunung Gajah, Klaten - Hiryanto; Sujarwo; Tristanti; Fitta Ummaya Santi (Postgraduate, University of Mataram, 2023)
Rocks such as metamorphic and sedimentary are natural constructions. Rocks in natural construction become elementary materials that form the landscape of the area, including in nature-based tourism objects, Bukit Cinta in Gunung Gajah, Klaten, Central Java. The purpose of this research is to describe the elements of rocks in the place. The study method used is descriptive qualitative method and tends to use analysis. The theoretical basis is used as a basic reference in preparing the study report to match the conditions in the field. In addition, the theoretical basis can also provide an overview of the background of the study as material for discussion. The ability to collect data is an important factor in determining the validation of the study conducted. Data collection in this case is obtained secondarily, namely through documents or literature studies. The results of the study found that there are 3 main supporters for the strong landscape in the tourist ojek of Gunung Gajah love hill. The three are metamorphic rocks observed there are fillic metamorphic relief, marble metamorphic rocks, and quartzite metamorphic rocks; limestone sedimentary rocks. Limestone can be used for building materials, road paving, and house foundations; and Diorte igneous rocks. Diorte igneous rocks can be used as home decoration.